Design and construction process in campus open spaces: A case study of Karadeniz Technical University - Ozkan, Doruk Gorkem; Alpak, Elif Merve; Var, Mustafa (PALGRAVE MACMILLAN LTD, 2017)
Universities comprise buildings in which education, teaching, research and practice are undertaken as well as physical structures with social and cultural activity spaces. They've a constantly evolving and changing structure in parallel to an increase in the number of students and the educational structures. Increasing number of physical structures result in failure to meet students' requirements for open space. Nevertheless, university campuses should ensure that students who do not know each other get to know each other and get used to the environment to which they are strangers by providing students with common living spaces. For this reason, it was considered to re-design an outdoor area (festival area) in Karadeniz technical university campus, where students can perform their extracurricular activities and increase their social relations with one another. As a result of the literature review, it was seen that most of the studies are either carried out only to design successful outdoor spaces for the needs of the users or the spaces designed by other people are assessed after use. Consequently, it was determined that there are certain deficits in determining whether the spaces designed in line with the decisions made by the researcher fulfil user needs. For this reason, it was aimed in this study to make the post-use evaluation of the production process after the outdoor design process of a campus outdoor space is completed by the researcher. The present study was conducted in Kanuni Park (festival area) in main campus of Karadeniz Technical University, which is currently used as a parking lot only and sometimes used as a concert venue at certain times of the year. The objective of the study was to realize spatial organization of the said study area so that it meets the students' needs and requirements, serves as a space where various activities take place, and provides facilities for a variety of uses (affordance) on a continuous basis, rather than at certain times of the year. Therefore, programming/design/construction/occupancy/post occupancy evaluation processes which comprise spatial development process were performed within Kanuni Park and such processes were evaluated.
Keywords: design and construction process; campus open spaces; university; SOCIAL-INTERACTION; OUTDOOR SPACES; URBAN DESIGN; Architecture; Public Administration; Urban Studies